Hubungan Pola Konsumsi Makanan Cepat Saji, Minuman Berpemanis, dan Asupan Serat dengan Kolesterol Darah pada Dewasa Muda: Associations of Fast-Food Consumption Patterns, Sugar-Sweetened Beverages, and Fibre Intake with Blood Cholesterol in Young Adult - Sari, Hesti Permata; Sulistyaning, Afina Rachma; Wicaksari, Sifa Aulia; Putri, Windi Prisria; Widyaningtyas, Elok (Universitas Airlangga, 2024)
Background: Hypercholesterolemia, defined as cholesterol levels of 200 mg/dl or above, is often attributable to lifestyle shifts, including changes in dietary habits, particularly noticeable in young adults. Objectives: This study seeks to establish the relationship between patterns of fast food and sugar-sweetened beverage (SSB) consumption, dietary fiber intake, and blood cholesterol levels in young adults. Methods: An observational, cross-sectional study was conducted on 100 participants, selected through purposive sampling. The selection criteria included age between 18-25, non-smokers, no prior diagnosis of dyslipidemia or CHD, no family history of dyslipidemia, and not currently on a diet. The Food Frequency Questionnaire (FFQ) was used to gather data on fast food and SSB intake, dietary fiber intake was assessed through food records, and cholesterol levels were measured using the Easy Touch GCU tool. The chi-square likelihood test and Spearman rank were used to analyze the data. Results: The study revealed that 48% of participants had cholesterol levels of â‰¥200 mg/dl. Descriptive analysis showed that 46% of participants frequently consumed fast food, 53% frequently consumed SSBs, and all participants had a daily fiber intake of less than 25 g. Bivariate analysis revealed significant correlations between cholesterol levels and patterns of fast-food consumption (p-value=0.000), SSB intake (p-value=0.000), and dietary fiber intake (p-value=0.019), all with a negative directional correlation. Conclusions: Young adults with cholesterol levels of â‰¥200 mg/dl were predominantly those who frequently consumed fast food and SSBs, and had a low intake of dietary fiber.